Intravitreal bevacizumab treatment for neovascular age-related macular degeneration and thromboembolic events. Issue 1 (January 2020) - Weinstein, Orly; Abu Tailakh, Muhammad; Lifshitz, Tova; Novack, Victor; Levy, Jaime
Background: Systemic complications of intravitreal anti-vascular endothelial growth factor agents are relatively uncommon but highly significant. Objectives: Primary objective : To assess the risk for thromboembolic events following intravitreal bevacizumab injection in neovascular age-related macular degeneration patients by a large population-based study. Secondary objective : To analyze the association between injection frequency and the risk for thromboembolic events, the time interval between the injection and the thromboembolic events, and the influence of chronic diseases on complications rate. Design: A retrospective cohort study. Methods: Consecutive neovascular age-related macular degeneration patients receiving intravitreal bevacizumab at Soroka University Medical Center from December 2005 to December 2013 were included. Thromboembolic events analyzed included acute coronary syndrome, acute myocardial infarction, stroke, deep vein thrombosis, and pulmonary embolism. The thromboembolic event rate was compared 2 years prior and 2 years after the initial intravitreal bevacizumab injection. Results: A total of 2102 patients were included. Acute coronary syndrome and stroke rate were higher 2 years after intravitreal bevacizumab (p = 0.03 and p = 0.01, respectively). No statistical significant difference was found for the rest of thromboembolic events. Patients older than 80 years and patients receiving less than six intravitreal bevacizumab injections were more likely to experience stroke. Patients with known cardiovascular risk factors before starting injections did not develop significant more thromboembolic events. Conclusion: In our study population, patients treated with intravitreal bevacizumab were significantly more likely to experience stroke during 2 years after first injection.